Kemampuan Bahasa Tulis pada Individu dengan Alzheimer: Kajian Neurolinguistik - Sholikhah, Nikmatus; Hariri, Tatang (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
Impaired brain function in individual with Alzheimer’s progressively affects to the cognitive and motor functions required to perform written language skills. This study aims to identify and describe the written skill in individual with Alzheimer’s through a case study approach. Data was obtained from a 56 years old elderly whose initials is KA and lives in PPSLU Potroyudan Jepara. Data collection techniques were carried out through documentation, observation, and interviews. Then, KA’s handwriting analysed using writing disorders theory through Neurolinguistic studies. The results showed that there are four forms of disturbance in KA’s written language, those are irregular writing, word omission in long sentences, letter omission, and letter replacement. The findings showed that Allzheimer which causes dysfunction in several parts of the brain also resulted in agraphia and a decrease in the syntactic complexity of writing.